Market Knowledge, Diversification and Export Expansion - Denis, Jean-Emile; Depelteau, Daniel (Journal of International Business Studies, 1985)
The research focuses on the export expansion process of small and middle-sized manufacturing firms and some of its correlates: diversification and geographical market distribution, means of acquiring information and modes of international distribution. The study reveals the overwhelming influence on export expansion of information acquired from business transactions as opposed to reliance on private or public information services. The impact of market diversification and its nature is confirmed. Policy implications are suggested.